INFLUÊNCIA DA FIBRONECTINA SOBRE A PROLIFERAÇÃO DE CARDIOMIÓCITOS - Bergami, Amanda Aparecida de Lima (2022)
Cardiovascular diseases are among the leading cause of death worldwide and Tissue engineering is a promising alternative for treatment, with scaffolds, cells and growth factors being the three factors that make up this area. Generally, scaffolds assist in cell adhesion, proliferation, differentiation and maturation, acting in a similar way to the native extracellular matrix. Fibronectin is one of the most important proteins constituted in the extracellular matrix and contributes significantly to cellular maintenance. The research group in which this work is inserted aims to evaluate the recellularization of the decellularized heart from the enrichment with fibronectin. Thus, the present study aimed to evaluate the influence of fibronectin on the cell proliferation of cardiomyocytes in vitro, by analyzing the proliferation and viability of (i) cardiomyocytes of the H9c2 lineage, (ii) cardiomyocytes isolated from the hearts of adult Swiss mice and (iii) neonates. The results showed that the presence of fibronectin did not influence cell viability and proliferation. From this, new proteins must be analyzed for this purpose, such as collagen, laminin, periostin and vitronectin.